2013
DOI: 10.1074/jbc.m112.388876
|View full text |Cite
|
Sign up to set email alerts
|

SET Protein Interacts with Intracellular Domains of the Gonadotropin-releasing Hormone Receptor and Differentially Regulates Receptor Signaling to cAMP and Calcium in Gonadotrope Cells

Abstract: Background: Mechanisms regulating signaling of mammalian GnRH receptor (GnRHR), which exhibits an atypical structure, are poorly known. Results: SET interacts with GnRHR, differentially impacts GnRHR coupling to calcium and cAMP signaling, and enhances GnRH stimulation of Gnrhr promoter activity. Conclusion:This represents the first identification of a GnRHR interacting partner that enhances its coupling to the cAMP pathway. Significance: SET is a novel regulator of GnRHR signaling.In mammals, the receptor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…3d, e and Extended Data Fig. 6 ) and others have shown that SET binds to positively charged amino acids in histone tails or cytoplasmic domains of membrane proteins 18 , 27 . According to the positive-inside rule for integral membrane proteins, the cytoplasmic domains of membrane proteins are enriched in positively charged amino acids for topological reasons 28 .…”
mentioning
confidence: 77%
“…3d, e and Extended Data Fig. 6 ) and others have shown that SET binds to positively charged amino acids in histone tails or cytoplasmic domains of membrane proteins 18 , 27 . According to the positive-inside rule for integral membrane proteins, the cytoplasmic domains of membrane proteins are enriched in positively charged amino acids for topological reasons 28 .…”
mentioning
confidence: 77%
“…Mutations in the gene encoding SET are linked to developmental delay and intellectual disabilities as well as to autosomal dominant 58 (MRD58), a form of mental retardation, characterized by significantly below average general intellectual functioning associated with delayed development, impairments in adaptive behavior, language delay and speech impairment [94][95][96]. Interestingly, SET interacts with intracellular domains of the gonadotropin-releasing hormone (GnRH) receptor and differentially regulates receptor signaling to cAMP and calcium in gonadotrope cells [97]. Notably, a recent study showed that SET expression is regulated by the neurohormone GnRH [98], providing a potential molecular basis for sex-specific differences in expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…SET protein directly binds with PP2Ac through its both N-terminus and C-terminus regions, and inhibits PP2A phosphatase activity [ 20 ]. The SET oncoprotein participates in the regulation of a wide variety of molecular processes [ 21 - 24 ]. Of importance, SET plays an oncogenic role modulating signaling pathways with high relevance in human cancer [ 25 ].…”
Section: Introductionmentioning
confidence: 99%